A novel approach to determine the effect of irrigation on temperature and failure of Ni-Ti endodontic rotary files - Sayed Ali Mousavi; Vida Kargar-Dehnavi; Sayed Amir Mousavi (Wolters Kluwer Medknow Publications, 2012)
Background: Nickel-titanium (Ni-Ti) rotary instrument files are important devices in Endodontics in root canal preparation. Ni-Ti file breakage is a critical and problematic issue and irrigation techniques were applied to decrease risk of file failure root. The aim of the present study was to compare the temperature gradient change of different irrigation solutions with Ni-Ti rotary instrument system during root canal preparation and also to define their effects on the file failure. Materials and Methods: A novel computerized instrumentation was utilized and thirty standard (ProFile #25/.04) files were divided into three groups and subjected to a filing in the root canal test. Changes in temperature on teeth under constant instrumental conditions with custom-designed computerized experimental apparatus were measured by using a temperature sensor bonded to the apical hole. A rotary instrument for canal preparation in three series of solution was used and the changes in temperature after each solution were compared. Finally, the file failure results were mentored according to each step of test. Comparisons were performed between group status clinically by using ANOVA (t) test, once the sample showed up normal and differences of P<0.01 were considered significant. All data collected were computerized and analyzed for frequency, distribution, and statistical description. Results: There was a decrease in the temperature of the instruments, which were immersed in 5% NaOCl, when compared with the water group (P<0.01). There was also a decrease in the temperature of the instruments immersed in water, when compared with the no solution group (P<0.01). Test results showed that sodium hypochlorite, water, or air of root canals does alter the properties of gradual temperature change and contributes to the failure of the instruments. Conclusion: By immersing the file in 5% NaOCl, the temperature gradient decreased and instrument failure was reduced.